ANALISIS TANGGUNGJAWAB PELAKU USAHA TERKAIT PEMADAMAN LISTRIK DI DAERAH DKI JAKARTA OLEH PT PERUSAHAAN LISTRIK NEGARA (PERSERO) BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Sonya Sonya; A.M. Tri Anggraini (Jurnal Hukum Adigama, 2019)
Some time ago, precisely on August 4, 2019 there was a sudden power outage that occurred in the Jakarta area. Regarding this power outage, consumers from PT. PLN (Persero) has rights that need to be accounted for as producers. How is the responsibility of business actors related to power outages in the DKI Jakarta area by PT. PLN (Persero) based on Law Number 8 of 1999 Concerning Consumer Protection? What legal remedies can be taken by consumers of electricity service users? The research method that I use is Normative accompanied by interviews. The author analyzes that the South Jakarta District Court Judge should see and consider Article 1365 of the Civil Code which explains that every act that violates the law and brings harm to others, obliges the person who caused the loss due to his mistake to replace the loss from the explanation of article above that the South Jakarta District Court Judge should have accepted the petello bello case which was harmed by PT PLN (Persero) which caused losses suffered by petro bello of Rp. 9,200,000. Then Law Number 30 Year 2009 Concerning Electricity Article 29 Paragraphs (1) and (2) which explains that the consumer's rights must be fulfilled by the PLN, but in reality the South Jakarta District Court Judges do not pay attention and do not consider the Article.